2002
DOI: 10.1034/j.1399-0004.2002.620406.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute intermittent porphyria in Sweden. Molecular, functional and clinical consequences of some new mutations found in the porphobilinogen deaminase gene

Abstract: Acute intermittent porphyria (AIP) is an autosomal dominant disorder caused by a partial deficit of porphobilinogen deaminase (PBGD), the third of eight enzymes in the haem biosynthetic pathway. The overt disease is characterized by neuropsychiatric symptoms that are often triggered by exogenous factors such as certain drugs, stress, and alcohol. The aim of this work has been to identify the underlying genetic defect in each AIP-affected family in order to provide early counselling to assist in the avoidance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 45 publications
6
52
0
3
Order By: Relevance
“…In support of this hypothesis, there have been well documented reports of a high prevalence of disorders such as schizophrenia (Böök et al 1980) and oral clefts (Nordström, 1995) in particular northern Swedish communities. More specifically, autosomal recessive disorders such as Sjögren Larsson syndrome (MIM 270200) (Jagell et al 1981) and Kostman's infantile agranulocytosis (MIM 202700) (Iselius & Gustavson, 1984) have been diagnosed at high frequency in the population of Skellefteå and adjoining regions, along with a wide range of autosomal dominant diseases that include acute intermittent porphyria (MIM 176000) (Floderus et al 2002), hereditary essential tremor (MIM 190300) (Larsson & Sjögren, 1960), torsion dystonia (MIM 128100) (Forsgren et al 1988), Best's macular dystrophy (MIM 153700) (Nordström & Barkman, 1977), amelogenesis imperfecta 2 (MIM 104500) (Backman & Holmgren, 1988), and amyloid polyneuropathy (FAPmet30) (MIM 176300) .…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, there have been well documented reports of a high prevalence of disorders such as schizophrenia (Böök et al 1980) and oral clefts (Nordström, 1995) in particular northern Swedish communities. More specifically, autosomal recessive disorders such as Sjögren Larsson syndrome (MIM 270200) (Jagell et al 1981) and Kostman's infantile agranulocytosis (MIM 202700) (Iselius & Gustavson, 1984) have been diagnosed at high frequency in the population of Skellefteå and adjoining regions, along with a wide range of autosomal dominant diseases that include acute intermittent porphyria (MIM 176000) (Floderus et al 2002), hereditary essential tremor (MIM 190300) (Larsson & Sjögren, 1960), torsion dystonia (MIM 128100) (Forsgren et al 1988), Best's macular dystrophy (MIM 153700) (Nordström & Barkman, 1977), amelogenesis imperfecta 2 (MIM 104500) (Backman & Holmgren, 1988), and amyloid polyneuropathy (FAPmet30) (MIM 176300) .…”
Section: Discussionmentioning
confidence: 99%
“…The G111R mutation, found in family D from São Paulo, was originally described in Europe (Gu et al, 1993). It was also reported in Slavic (Rosipal et al, 1997), French , British (Whatley et al, 1999), Swedish (Andersson et al, 1995;and Floderus et al, 2002) and Polish patients . In Argentina, the G111R mutation was detected in 12 families (De Siervi et al, 1999) which seem Normal individuals showed one band whereas a heteroduplex was observed in asymptomatic gene carriers.…”
Section: Discussionmentioning
confidence: 95%
“…Most of them are point mutations with high heterogeneity except for mutation associated with so-called founder effect, e.g. mutation R1 98W identified in northern Sweden [4,18,19].…”
Section: Acute Intermittent Porphyriamentioning
confidence: 99%
“…The prevalence of AIP in Europe is 1/75 000 inhabitants; in northern Sweden 1/1000 due to a founder effect [1,4] and in Finland 3/100 000 [5]. AIP prevalence in Argentina is about 1/125 000 inhabitants [6].…”
Section: Epidemiology Datamentioning
confidence: 99%